Common genetic variants at the CRAC1 (HMPS) locus on chromosome 15q13.3 influence colorectal cancer risk. - Jaeger, E; Webb, E; Howarth, K; Carvajal-Carmona, L; Rowan, A; Broderick, P; Walther, A; Spain, S; Pittman, A; Kemp, Z; Sullivan, K; Heinimann, K; et al. (2008)
We mapped a high-penetrance gene (CRAC1; also known as HMPS) associated with colorectal cancer (CRC) in the Ashkenazi population to a 0.6-Mb region on chromosome 15 containing SCG5 (also known as SGNE1), GREM1 and FMN1. We hypothesized that the CRAC1 locus harbored low-penetrance variants that increased CRC risk in the general population. In a large series of colorectal cancer cases and controls, SNPs near GREM1 and SCG5 were strongly associated with increased CRC risk (for rs4779584, P = 4.44 x 10(-14)).